A small plant with big benefits: Fenugreek (Trigonella foenum‐graecum Linn.) for disease prevention and health promotion. Issue 6 (27th April 2017) - Nagulapalli Venkata, Kalyan C.; Swaroop, Anand; Bagchi, Debasis; Bishayee, Anupam
Abstract : Fenugreek ( Trigonella foenum‐graecum Linn.), a short‐living annual medicinal plant, is used extensively in various parts of the world as herb, food, spice, and traditional medicine. This review summarizes and critically analyzes the current available literature to understand the potential benefits of fenugreek for disease prevention and health promotion with special emphasis on underlying cellular and molecular mechanisms. Current challenges and new directions of research on fenugreek are also discussed. Abstract : Plant‐derived natural products have long‐standing utility toward treating degenerative diseases. It is estimated that about two‐thirds of world population depend on traditional medicine for primary medical needs. Fenugreek ( Trigonella foenum‐graecum Linn.), a short‐living annual medicinal plant belonging to Fabaceae family, is used extensively in various parts of the world as herb, food, spice, and traditional medicine. Fenugreek is considered as one of the oldest medicinal plants and its health‐promoting effects have been cited in Ayurveda and traditional Chinese medicine. The investigations into the chemical composition and pharmacological actions have seen a renaissance in recent years. Extensive preclinical and clinical research have outlined the pharmaceutical uses of fenugreek as antidiabetic, antihyperlipidemic, antiobesity, anticancer, anti‐inflammatory, antioxidant, antifungal, antibacterial, galactogogue and for miscellaneous pharmacological effects, including improving women's health. The pharmacological actions of fenugreek are attributed to diverse array of phytoconstituents. The phytochemical analysis reveals the presence of steroids, alkaloids, saponins, polyphenols, flavonoids, lipids, carbohydrates, amino acids, and hydrocarbons. This review aims to summarize and critically analyze the current available literature to understand the potential of fenugreek for disease prevention and health improvement with special emphasis on cellular and molecular mechanisms. Current challenges and new directions of research on fenugreek are also discussed.